The Moderating Role of Self Efficacy on the Effect of Digital Literacy on Entrepreneurial Intention - Hidayat, Nur; Sugiardi, Sigit; Gunawan, Setyo; Rawa, Ricola Dewi; Puspitasari, Nindy (Universitas Tanjungpura, 2025)
The present study has been designed to examine the effect of digital literacy and self-efficacy on entrepreneurial intention, as well as the moderating role of self-efficacy in the relationship between digital literacy and entrepreneurial intention in students of the Faculty of Economics and Business at Universitas Panca Bhakti. The research method utilizes a quantitative approach, employing a questionnaire that was distributed to 200 students who were selected through purposive sampling. The collected data is then analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM). The findings of the study indicated that Digital Literacy exerts a substantial influence on Entrepreneurial Intention, while Self-efficacy also demonstrated a significant impact on Entrepreneurial Intention. However, the hypothesis that self-efficacy moderates the effect of digital literacy on entrepreneurial intention remains unproven.